Peran Intervensi Psikoedukasi dalam Meningkatkan Empathic Concern pada Remaja Awal: Systematic Literature Review - Aris, Riska Aulyanti; Harum, Akhmad; Aswar, Aswar; Fitri, Qawiyyan (Universitas Muhammadiyah Magelang, 2026)
Empathic concern is an affective component of empathy that plays a crucial role in the social and emotional development of adolescents. The decline of empathic concern among adolescents has become a global concern, marked by a weakening of emotional caring in younger generations toward others across various social contexts. In Indonesia, the high prevalence of relational problems among adolescents indicates weakening socio-emotional competence, including low levels of empathic concern among students. This study aims to conduct a systematic literature review on the role of psychoeducational interventions in improving empathic concern among early adolescent students. Data were collected through searches of three electronic databases covering publications from 2015 to 2025, yielding 14 articles that met the predetermined inclusion criteria. Data analysis employed a narrative synthesis approach to group and synthesize findings based on psychoeducational intervention characteristics, population, and measured outcomes. The findings indicate that the majority of psychoeducational interventions play a role in enhancing students' empathic concern, with participatory methods such as role-playing, reflective discussion, and social simulation yielding more optimal outcomes compared to conventional approaches. Psychoeducational interventions designed in a participatory, contextual, and sustained manner represent a promising approach to strengthening empathic concern among students in educational settings.